Beyond Inclusion and Exclusion: Jewish Experiences of the First World War in Central Europe - Crouthamel, Jason (Berghahn Books, Incorporated, 2018)
Beyond Inclusion and Exclusion -- Copyright Page -- Contents -- Figures and Tables -- Acknowledgments -- Introduction -- Part I. At the Margins -- Chapter 1. Hopes and Disappointments -- Chapter 2. Habsburg Jews and the Imperial Army before and during the First World War -- Chapter 3. The "Stepchildren" of the Kaiserreich -- Part II. Relations -- Chapter 4. Rethinking Jewish Front Experiences -- Chapter 5. "Being German" and "Being Jewish" during the First World War -- Chapter 6. In the Shadow of Antisemitism -- Chapter 7. The Social Engagement of Jewish Women in Berlin during the First World War -- Chapter 8. "My Comrades Are for the Most Part on My Side" -- Part III. Representation -- Chapter 9. Blind Spots and Jewish Heroines -- Chapter 10. Agnon on the German Home Front in In Mr Lublin's Store -- Part IV. Contested Memories -- Chapter 11. Paper Psyches -- Chapter 12. Narrative Negotiations -- Afterword -- Index